Dual actions of albumin packaging and tumor targeting enhance the antitumor efficacy and reduce the cardiotoxicity of doxorubicin in vivo - Zheng K (Dove Medical Press, 2015)
Ke Zheng,1 Rui Li,2 Xiaolei Zhou,2 Ping Hu,2 Yaxin Zhang,2 Yunmei Huang,3 Zhuo Chen,2 Mingdong Huang2 1College of Chemistry, Fuzhou University, Fuzhou, People’s Republic of China; 2State Key Laboratory of Structural Chemistry, Fujian Institute of Research on the Structure of Matter, Chinese Academy of Sciences, Fuzhou, People’s Republic of China; 3Fujian Academy of Integrative Medicine, Fujian University of Traditional Chinese Medicine, Fuzhou, People’s Republic of China Abstract: Doxorubicin (DOX) is an effective chemotherapy drug used to treat different types of cancers. However, DOX has severe side effects, especially life-threatening cardiotoxicity. We herein report a new approach to reduce the toxicity of DOX by embedding DOX inside human serum albumin (HSA). HSA is further fused by a molecular biology technique with a tumor-targeting agent, amino-terminal fragment of urokinase (ATF). ATF binds with a high affinity to urokinase receptor, which is a cell-surface receptor overexpressed in many types of tumors. The as-prepared macromolecule complex (ATF–HSA:DOX) was not as cytotoxic as free DOX to cells in vitro, and was mainly localized in cell cytosol in contrast to DOX that was localized in cell nuclei. However, in tumor-bearing mice, ATF–HSA:DOX was demonstrated to have an enhanced tumor-targeting and antitumor efficacy compared with free DOX. More importantly, histopathological examinations of the hearts from the mice treated with ATF–HSA:DOX showed a significantly reduced cardiotoxicity compared with hearts from mice treated with free DOX. These results demonstrate the feasibility of this approach in reducing the cardiotoxicity of DOX while strengthening its antitumor efficacy. Such a tumor-targeted albumin packaging strategy can also be applied to other antitumor drugs. Keywords: amino-terminal fragment of urokinase, urokinase receptor, drug carrier, human serum albumin, doxorubicin, cytotoxicity